A prototype active-matrix OLED using graphene anode for flexible display application. Issue 1 (2nd January 2020) - Kwon, O Eun; Shin, Jin-Wook; Oh, Himchan; Kang, Chan-mo; Cho, Hyunsu; Kwon, Byoung-Hwa; Byun, Chun-Won; Yang, Jong-Heon; Me Lee, Kang; Han, Jun-Han; Sung Cho, Nam; Hyuk Yoon, Jong; et al.
Abstract : From the very first time that graphene was used as a transparent electrode for OLED applications, the emergence of active-matrix (AM)-graphene OLED displays has been envisioned. Realizing this expectation, however, turned out to be difficult. Two obstacles are the growth and transfer of a large-area graphene film and the patterning of a graphene film into pixels. To solve these problems, a process of patterning a graphene film without surface contamination was developed. The fabrication of OLED panels by the patterned graphene anode on Gen 2(370 × 470 mm)-sized and flexible substrates was successfully demonstrated. In this work, oxide TFT arrays were combined as a switching backplane, and a pixelated graphene OLED was used as an emissive layer, to realize AM-graphene OLED displays. To explore the technical feasibility of flexible AM-graphene OLED displays, the aforementioned components were formed on a flexible substrate. For commercial-level production, all the processes that were used were chosen to be compatible with the conventional display processes.